126 EMS response time to sports injuries: a role for on-scene responders. (5th May 2020) - Bovbjerg, Viktor; Johnson, Sam; Norcross, Marc
Abstract : Statement of Purpose: Emergency medical services (EMS) often respond to injuries sustained during team athletics and sports. The interval between injury and EMS arrival allows on-scene responders to provide immediate care. Methods/Approach: We identified EMS runs associated with team or group sports (ICD-10 activity code Y93.6x), to a school or an athletic field or facility, using National Emergency Medical Services Information System (NEMSIS) 2017 data. We calculated EMS response times to scene as the difference between dispatch time and on-scene time. Initial patient acuity was defined as 'green' (lower acuity), 'yellow' (emergent), 'red' (critical), or 'black' (deceased). We compared mean response time by patient acuity group. Results: Of 1107 EMS runs identified, initial acuity for the majority was green (764, 70.2%), with a substantial yellow group (302, 27.8%), and relatively few red cases (22, 2.0%); there were no on-scene fatalities. Response times did not differ significantly by acuity. Approximately one quarter (292, 27.0%) of EMS responses were within five minutes, with greater proportions in the 5–10 minute (472, 43.6%) and 10+ minute (319, 29.5%) range; all but 76 responses (7%) were greater than two minutes. Conclusions: In over 90% of EMS responses identified in the 2017 NEMSIS data involving response to a team sporting or athletic event, response time was greater than 2 minutes; approximately 75% were greater than 5 minutes. For every injury, but particularly for emergent and critical injuries, this represents an important interval during which patient assessment, stabilization, treatment, and packaging by on-scene responders could improve outcomes. Emergency action plans can formalize pre-EMS on-scene emergency response in athletic settings. Significance and Contributions to Injury and Violence Prevention Science: The presence of trained and equipped on-scene responders (e.g. athletic trainers, coaches) would enable effective initial care during the interval until EMS arrival, and improve patient outcomes.